Landscapes of loss : the national past in postwar French cinema - Greene, Naomi, 1942- (Princeton University Press, 2001)
In this book, Naomi Greene makes new sense of the rich variety of postwar French films by exploring the obsession with the national past that has characterized French cinema since the late 1960s. Observing that the sense of grandeur and destiny that once shaped French identity has eroded under the weight of recent history, Greene examines the ways in which French cinema has represented traumatic and defining moments of the nation's past: the political battles of the 1930s, the Vichy era, decolonization, the collapse of ideologies. Drawing upon a broad spectrum of films and directors, she shows how postwar films have reflected contemporary concerns even as they have created images and myths that have helped determine the contours of French memory. This study of the intricate links between French history, memory, and cinema begins by examining the long shadow cast by the Vichy past, and shifting political and historical perspectives toward the nation's more distant past, which also emerged in these years. Finally, the mood of nostalgia and melancholy that appears to haunt contemporary France is analyzed in the context of films about the nation's imperial past as well as those that hark back to a "golden age," a remembered paradis perdu, of French cinema itself.